An evaluation of rural development strategies in the Builsa North District of Ghana - Anyatewon, Douglas Kwesi (2016)
A thesis submitted to The School of Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of Master of Science in Development Policy and Planning, 2015